2011
DOI: 10.1055/s-0031-1275356
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Resting and Postexercise Heart Rate Measures

Abstract: In this study, we compared the reliability of short-term resting heart rate (HR) variability (HRV) and postexercise parasympathetic reactivation (i.e., HR recovery (HRR) and HRV) indices following either submaximal or supramaximal exercise. On 4 different occasions, beat-to-beat HR was recorded in 15 healthy males (21.5 ± 1.4 yr) during 5 min of seated rest, followed by submaximal (Sub) and supramaximal (Supra) exercise bouts; both exercise bouts were followed by 5 min of seated recovery. Reliability of all HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
146
6
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(178 citation statements)
references
References 32 publications
18
146
6
8
Order By: Relevance
“…Al Haddad and colleagues [1] found similar reliability of ΔHRR to this study at 15-32% but current ΔHRR data is consistent with previous studies that have consistently concluded improved reliability of ΔHRR with longer recovery durations [2,4]. Most HRR studies focus on the delta change from peak exercise HR as this is the method implemented to identify abnormal HRR (for example HRR of <12 beats) and has been used since the late 1990's [8].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Al Haddad and colleagues [1] found similar reliability of ΔHRR to this study at 15-32% but current ΔHRR data is consistent with previous studies that have consistently concluded improved reliability of ΔHRR with longer recovery durations [2,4]. Most HRR studies focus on the delta change from peak exercise HR as this is the method implemented to identify abnormal HRR (for example HRR of <12 beats) and has been used since the late 1990's [8].…”
Section: Discussionsupporting
confidence: 89%
“…HRR after submaximal exercise has been previously reported to show high intra-class correlation coefficient (ICC) values, for exercise protocols above 65% of age-predicted maximum heart rate (APMHR), but highest values with protocols requiring at least 80% APMHR in healthy International Journal of Sports Medicine 2014, 35: 135-38 individuals [2]. However, other investigators found no difference in HRR reliability following submaximal and supramaximal exercise [1]. A recent review supports the use of HRR as a valuable tool to monitor changes in training status in athletes and less trained individuals, which would also encompass clinical populations, but they highlighted the need for the standardisation of HRR protocols [10].…”
Section: Introductionmentioning
confidence: 99%
“…Ln rMSSD has previously been shown to have greater reliability and validity than spectral indices of HRV over short assessment periods. 18,19 The coefficient of variation for LnrMSSD was 10 % respectively. 6 Statistical Analyses…”
Section: Methodsmentioning
confidence: 98%
“…The reliability of HRV and HRR measures between exercise sessions may be described as moderate; reliability depends partly on e.g. exercise mode and the chosen parameters and analysis methods (Al Haddad et al 2011;Bosquet et al 2008). …”
Section: Short-term Measurements Of Hrvmentioning
confidence: 99%
“…Al Haddad et al (2011) investigated the reliability and repeatability of resting HRV, post-exercise HR recovery and different HRV indices on four different occasions. They found a lower coefficient of variation (CV) for HFPln during rest (13 %) when compared to immediate 5 minute recovery after supramaximal bouts of exercise (26 %).…”
Section: Limitationsmentioning
confidence: 99%